BRIEF RECOMMENDATIONS AND SCIENTIFIC SUMMARY FOR STUDENTS IN LEARNING VOCAL ART - Xodjakulov Bakhodir Xudoykulovich; Akbarova Mohigul Gulomovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation. Singing is one of the most delicate and labor-intensive forms of art, and the article provides some tips for those in the field, as well as guidelines on vocal science for students studying in this field. This article highlights what you should focus on in vocal performance.